1999
DOI: 10.1002/(sici)1097-0282(19990415)49:5<373::aid-bip4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Angular variances for internal bond rotations of side chains in GXG-based tripeptides derived from13C-NMR relaxation measurements: Implications to protein folding

Abstract: The study of backbone and side‐chain internal motions in proteins and peptides is crucial to having a better understanding of protein/peptide “structure” and to characterizing unfolded and partially folded states of proteins and peptides. To achieve this, however, requires establishing a baseline for internal motions and motional restrictions for all residues in the fully, solvent‐exposed “unfolded state.” GXG‐based tripeptides are the simpliest peptides where residue X is fully solvent exposed in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This hierarchy ranges from picoseconds to nanoseconds to microseconds to milliseconds and slower. NMR relaxation studies, which are most sensitive to motions occurring on the nanosecond to picosecond time scales, on small GXG tripeptides devoid of folded structure revealed that internal motions for backbone C α H and NH groups fall in the 70‐ to 100‐psec range (Mikhailov et al 1999), whereas in protein GB1, internal motions for backbone groups fall in the subnanosecond to 5‐nsec range, as well as in the picosecond range. Internal motions on the picosecond time scale were mostly omitted from this discussion primarily because these faster time scale motions are least accurately determined as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…This hierarchy ranges from picoseconds to nanoseconds to microseconds to milliseconds and slower. NMR relaxation studies, which are most sensitive to motions occurring on the nanosecond to picosecond time scales, on small GXG tripeptides devoid of folded structure revealed that internal motions for backbone C α H and NH groups fall in the 70‐ to 100‐psec range (Mikhailov et al 1999), whereas in protein GB1, internal motions for backbone groups fall in the subnanosecond to 5‐nsec range, as well as in the picosecond range. Internal motions on the picosecond time scale were mostly omitted from this discussion primarily because these faster time scale motions are least accurately determined as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides adopt random‐coil conformations according to CD measurements 22. Since the conformational changes required for end‐to‐end contact derive from fast rotations about the NC α and C α C bonds,23 and since different α substituents are expected to hinder these bond rotations to a different degree, we expected different collision frequencies when the probe and the quencher are separated by different amino acids. This arrangement should allow us to correlate the collision frequency with the type of amino acid and thereby build up a flexibility scale (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The meaning of the best-fit order parameters S f 2 extracted from fits using the LS-2 and -3 models in cases where slow side-chain dynamics is present is discussed below. Theoretical treatments which draw the connection between the model-free parameters and more fundamental quantities describing side-chain torsional dynamics have been presented in a number of recent papers. …”
Section: Model-free Approaches To Analysis Of Spectral Densitiesmentioning
confidence: 99%